Medications of medieval monastery medicine - Katarzyna Mądra - Gackowska; Marcin Gackowski; Emilia Główczewska-Siedlecka; Zygmunt Siedlecki; Sylwia Ziółkowska (Kazimierz Wielki University, 2018)
Herbal medicine has accompanied man since the dawn of time. For various ailments and health problems, help was sought in the surrounding nature. Ancient civilizations have greatly contributed to the development of phytotherapy, identifying and describing numerous species of medicinal plants. Plant raw materials have become the foundation of medieval medicine. The revival in herbal medicine has been observed since the sixth century with the emergence of monasteries, where the gardens in which the medicinal plants were grown were established. Monastic schools were also established, monks broadened their skills by studying and copying ancient books, preparing medicines of natural origin according to secret prescriptions used to heal the sick. Although the Middle Ages are often considered dark ages, many achievements of the then phytotherapy have been recorded on the pages of history and a man use them to this day.